PENINGKATAN HASIL BELAJAR SISWA PADA MATA PELAJARAN DENDANG DENGAN MENGGUNAKAN METODE BELAJAR MANDIRI DI SMK NEGERI 7 PADANG - Lusiana, Herlin; Lumbantoruan, Jagar (SENDRATASIK UNP, 2019)
Abstract The purpose of this study is to find out whether the use of independent learning method can improve students learning outcomes and to provide solutions for teachers in time management problems on Dendang subject. The type of studywas a qualitative with using descriptive analytical methods. The main instrument in this study was the researcher and it was assisted by supporting instruments such as recording device, camera, infocus and stationery. Techniques data collection were done by doing observation, documentation, interviews and documentation. Techniques of data analysis were carried out by doing reduction, presentation and drawing conclusion of data. The result shows that the independent learning method can improve students learning outcomes in the class XI of Karawitan Department in SMK 7 Padang on Dendang subject. This method is considered appropriate because it can optimize the use of time and material in Dendang subject. The explanation of material and practice can be achieved optimally because the students can also take advantage of study time outside the classroom in groups. The effect is the students can exchange ideas with their friends and are more flexible to improve their skills. Keywords: enhancement, learning outcomes, dendang subjects, self-learning methods